2020
DOI: 10.1007/s42399-020-00582-9
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Health and Stress in Pregnant Women During the Covid-19 Pandemic

Abstract: Stress is one of the effective factors in the occurrence of negative effects during pregnancy that can cause adverse outcomes such as preterm delivery and reduced intrauterine growth of the fetus in pregnant women. Therefore, one of the serious concerns during the COVID-19 pandemic is the physical health and mental health of pregnant women. This study aimed to evaluate the physical health status with the spiritual and mental health of pregnant women during the COVID-19 pandemic. The study is a descriptive stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 28 publications
0
26
0
1
Order By: Relevance
“…Nodoushan et al [ 31 ] evaluated the spiritual and mental health of pregnant women and COVID-19 anxiety during the pandemic in Iran, and found direct and significant association. In Pakistan, 36% of pregnant women interviewed stated the perception that the COVID-19 pandemic had a large impact on their mental health [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nodoushan et al [ 31 ] evaluated the spiritual and mental health of pregnant women and COVID-19 anxiety during the pandemic in Iran, and found direct and significant association. In Pakistan, 36% of pregnant women interviewed stated the perception that the COVID-19 pandemic had a large impact on their mental health [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Corbett et al (2020) [24] showed that most pregnant women (83.1%) did not worry about their health status before the pandemic of COVID-19, but during the pandemic, 50.7% were worried about their health status most of the time. Concerns of pregnant women may be related to the fact that they do not have access to their relatives if they needed, and many pregnant women may have concerns about lack of family and social support due to distancing measures [25]. In the first days of COVID-19 pandemic in Iran, one hospital in Ahvaz, where a large number of women receive intrapartum care, was designated as the center for patients with COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that COVID-19 during pregnancy is associated with higher rates of caesarean sections [ 8 , 9 ]. Generally, psychological distress is believed to play an important role in the occurrence of adverse pregnancy outcomes, preterm delivery included [ 10 , 11 , 12 ]. Although advanced age and comorbidities are the greatest risk factors of developing serious medical conditions and even death due to coronavirus-induced bilateral pneumonia [ 13 ], some physiological changes in pregnancy also increase susceptibility to infections and encourage rapid progression to respiratory failure.…”
Section: Introductionmentioning
confidence: 99%